From Micro to Nano: Grinding Natural Magnetite Ore for Microalgae Harvesting - Michael Schobesberger; Simone Helmhagen; Stefan Mende; Sonja Berensmeier; Paula Fraga-García (Magnetochemistry, 2023)
Microalgae represent a promising feedstock for sustainable biomass and energy. The low cell concentration after cultivation, however, limits the current application fields. Magnetic microalgae harvesting is a recent approach to overcome the economic limitations of exploiting this natural resource. Accordingly, different particle types have been applied, mainly synthetically produced magnetic nanoparticles, though none on an industrial scale. Particle sizes between a few micrometers and a few nanometers have not been tested. We expected 200–500 nm to be advantageous for harvesting and as a compromise between the highly available surface and good separation properties. However, this intermediate magnetite particle size between the micro- and nano-scale cannot be reached via chemical synthesis. Therefore, we ground natural magnetite ore in a planetary ball mill and an agitator bead mill producing particles in the targeted size range. Applying ore particles ground from ~6 µm to 250 nm yields harvesting efficiencies comparable to synthetically produced nanoparticles (Ø ~ 10 nm), with only half the BET surface. Complete harvesting of saline microalgae Microchloropsis salina is possible with ground particles at alkaline pH. We demonstrate the feasibility of a harvesting process with natural, low-cost, easily separable, and readily available magnetite ore particles as a promising step towards exploiting valuable microalgal products in life sciences.